COVID-19, fintech, and the recovery of micro, small, and medium-sized enterprises: Evidence from Bangladesh - Monzur Hossain; Tahreen Tahrima Chowdhury (Asian Development Bank Institute (ADBI), 2022)
This study assesses the impact of the COVID-19 pandemic on micro, small, and medium-sized enterprises (MSMEs) and the role of Fintech, in particular mobile financial services (MFS), in their recovery from COVID-induced losses. The study uses data from a survey of 216 MSMEs from Bangladesh Small and Cottage Industries Corporation (BSCIC) industrial estates in Bangladesh during January to March 2021. Our results suggest that firms have been recovering gradually after the withdrawal from lockdown in June 2020. So far, 80% of production of the firms compared to pre-COVID levels had recovered by the end of December 2020. We use instrumental variable regression to assess the impact of the use of MFS on firms' production, sales, and profit for three periods: lockdown (March-May 2020), limited lockdown (June-September 2020) and the reopening period (October-December 2020). We find a significant and positive impact from the use of MFS on the production, sales, and profit of firms during this pandemic. The results indicate that the use of digital finance facilitates firms' production through ensuring a stable supply of raw materials and sales that have prompted them to recover faster. However, the concern is that only about 31% of our sample firms use MFS for their businesses and an even lower proportion of firms are accustomed to using an online platform. Therefore, more incentives and supportive policies are needed to motivate MSMEs to use digital finance and online platforms to stay active in operations, particularly during the pandemic.
Keywords: D20; D22; G10; G20; 330; fintech; micro; small; and medium-sized enterprises; MSMEs; Bangladesh Small and Cottage Industries Corporation Estates; BSCIC; COVID-19; firm recovery; Bangladesh